Incidence of Helicobacter pylori Infection in District Haripur Khyber Pakhtunkhwa - Taimoor Akhtar, Sumaira Sarwar, Afsheen Ishfaq, Imran Haider, Qurat ul Ain Zia, Ayesha Kanwal, Maimoona Sabir (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Helicobacter pylori (H. pylori) is a Gram-negative, microaerophilic bacteria residing in stomach area, sometime presence of H. pylori does not demonstrate symptoms and causes disease to the host. H. pylori possibly the most common human pathogen, 60% of the world’s adult population’s guts are infested by this pathogen. Aim: Aim of study was to identify H. pylori in different age groups of Haripur district and examine different parameters associated with H. pylori. Method: Sero-prevalance rate of H. pylori among 150 individuals were analyzed using diaspot kit (Koeman Group of Companies.). Correlation of different parameters such as age group, occupation, gender, foods, water type consumption, sign and symptoms were analyzed in H. pylori infected individuals. The entire samples were collected from DHQ Haripur. All the methods were adopted as per manufacturer protocol using diaspot kit for H. pylori infection. Findings: Current study showed 85(56.6%) were positive samples while 65(43.3%) were negative. Among them, 48(56.4%) male and 37(43.5%) female were positive for H. pylori infection. Ratio of positive cases in age groups ranging from 20-30, 31-40, 41-50 and 51-60 were 21.1%, 31.7%, 24.7% and 22.3% respectively. Housewives (21.4%) employer (54.1%) and students were 24.7% positive for H. pylori. 65% of individual were found positive whose source of drinking water was tube well; water from bore well users were 55% positive and 43% filter users were positive for H. pylori. Among 150, 102(68%) were using spicy foods and remaining 48(32%) were using less spicy foods. 57(38%) of patients were on treatment of H. pylori while the 93(62%) were not taking treatment, results found that 85(56.6%) of individuals were positive while the 65(43.3%) found to be negative for the presence of H. pylori. Conclusion: Various epidemiological features like unhygienic food, increasing age, gender, and water type were also positively associated with H. pylori. Besides that, occupation and spicy food were also directly related to H. pylori. Keywords: Helicobacter pylori, Gram-negative bacteria, Incidence rate, Haripur, Khyber-Pakhtunkhwa